A Geospatial Technology based Approach to Study the Fire-Fighting Preparedness of a Library: A Case Study for the Central Library of The University of Burdwan, Bardhhaman, West Bengal - Laha, Banani; Mahato, Somnath; Pahari, Deb Prakash; Bose, Anindya (Journal of Information and Knowledge, 2022)
Libraries are particularly vulnerable to high fire load and therefore fire-fighting preparedness is an important aspect of library management. Suitable contingency plans are necessary to protect the educational and archival resources from irreparable damage. The present work accentuated the expediency of Geographical Information System (GIS) application using Computer Aided Design (CAD) model and in fire-fighting preparedness focussed on library facilities at the Central library of The University of Burdwan, West Bengal, India as a case study. The purpose of this work is to review current legislation and guidelines on fire safety in library facilities according to Indian Standard, and analyze the present situation in terms of existing infrastructure and facilities at the Burdwan University Central library (BUCL). With this, the fire emergency service response in GIS environment finally presents the findings of the case study to assess the provision of these requirements in BUCL. This Paper presents a detailed study on the fire preparedness analysis of the library with recommendations categorized in different levels of cost analysis, this work would be effective for successfully analysing the fire-fighting preparedness inside as well as outside of library facilities; the recommendations are also applicable to and can be followed as per need and available fund by other libraries.